The Mapping of Quality Tourists Prospects for Indonesia’s Tourism Markets - Addin Maulana; RR Chamma Fitri Putri Pradjwalita Koesfardani; I Dewa Gede Richard Alan Amory (Bina Nusantara University, 2020)
The research aimed to identify which countries could be segmented as a potential tourism market for Indonesiato increase quality tourists. It applied quantitative methods with descriptive statistical analysis techniques todescribe the average expenditure per visit and the length of stay. It was conducted by modifying the quadrantmodel. The result shows that there are countries included in the market with the prospect of quality tourists.Those are Saudi Arabia, Netherlands, Sweden, Switzerland, Belgium, Russia, France, Germany, Austria, Finland,Italy, Spain, Norway, Denmark, Canada, United Kingdom, New Zealand, USA, Portugal, Egypt, Pakistan, andAustralia. The government needs to optimize those countries to become the main market. Therefore, the revenuefrom the tourism sector can be better optimized.